Indonesian economic diversification as an emerging markets country to drive economic growth - Hasan, Zulfikar (INOVASI, 2021)
Indonesia's economic growth as an emerging market country can be determined from various variables to be measured. For this study, the authors take the variables of economic growth, infrastructure development, regional economic development, and Special Economic Zones to encourage economic diversification. Economic diversification is needed to increase regional income and increase economic growth, in addition to reducing poverty and creating job opportunities. Economic diversification needs to be done with various policies that can have a good impact on society, one of the most important things to do is improve good infrastructure, especially in rural areas. Most researchers have raised the theme of economic growth by linking poverty levels, but the authors are very interested in linking with infrastructure, regional economies, and also special economic zones. The research used in this paper combines qualitative and quantitative research, where qualitative research looks at the policies that have been and will be made by the central government to support economic diversification. Meanwhile, quantitative research relates more to the effect of economic growth with infrastructure and regional budgets. The results of the author's research indicate that there is a close relationship between economic growth and infrastructure development, where there is a positive relationship between these two variables. Meanwhile, for regional economic development, the central government has provided a stimulus that continues to increase every year. Special Economic Zones are also built based on budget rather than APBN and APBD according to budget optimization from the government.